PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS ARTIFICIAL INTELLIGENCE BAGI GURU MADRASAH IBTIDAIYYAH - herwani, suci; Aiunzzahro, Izza; Surayya, Arini Isna (GERVASI: Jurnal Pengabdian kepada Masyarakat, 2025)
Learning media is one of the most successful supports for learning because it helps teachers deliver material more effectively and interestingly, and supports better interaction between teachers and students. Training in creating artificial intelligence (AI)-based learning media for Madrasah Ibtidaiyyah teachers is needed to increase the use of technology and media in accordance with the curriculum and student needs. The aim of this service is to provide training in creating artificial intelligence-based learning media for madrasah ibtidaiyyah teachers. The service method is service learning with four stages, namely, investigation, preparation, action and reflection. The result of the service is that training participants are given material related to artificial intelligence-based learning media, namely Canva, then participants are asked to practice making exercises or quizzes using Canva. The training participants enthusiastically practiced making quizzes with Canva and hope that similar training can be held again.